Off-centered-symmetry-based band structure modulation of hexagonal WO3. (11th June 2019) - Zhu, Feng; Ma, Chunlan; Gu, Lingjun; Chen, Gaoyuan; Zhang, Jiayong; Cong, Shan; Zhao, Zhigang; Zhang, Xiaohua
Abstract: The accurate band gap of 2.24 eV for hexagonal WO3 is obtained by adopting the revised Heyd–Scuseria–Ernzerhof screened hybrid functional. The large band gap is a result of the off-centered symmetry where the W atom forms two short and two long bonds with four neighboring in-plane O atoms. By adding/removing electrons into/from the crystal, the effect of charge doping is investigated. With introducing electrons, the off-centered symmetry gets weakened with a slight narrowing in band gap. However, the doping lifts the Fermi level into the conduction band, inducing an increase in transition energy for electrons. Similarly, the hole doping also results in a remarkable increase in the transition energy. Such band structure modulation can be used in high efficient photoabsorption, photocatalysis and surface-enhanced Raman spectroscopy.